Founding Member of Cultural Organizations and Research Labs/Member of KilowArt platform Artistic Organizer - Antoniou, Klitsa (My University, 2026)
Founding Member of Cultural Organizations and Research Labs Member of KilowArt platform Artistic Organizer Αστική Μη Κερδοσκοπική Εταιρεία Ptolemaida Greece